Electrophysiological analysis of distal, proximal, and dual compression of the median nerve - Qiongfang Zhang; Yongfeng Liu; Jinhuan Zhang; Yirong Chen; Xingxian Huang; Haibo Yu (IBRO Neuroscience Reports)
Objective: Both distal and proximal compression of the median nerve can lead to hand numbness inpatients.This study aimed to dissect the electrophysiological characteristics of median nerve motor fibers inpatients with carpal tunnel syndrome (CTS) caused by distal median nerve compression, C8 - T1 nerve root - type cervical spondylosis (CRS) resulting from proximal median nerve compression, and double - compression syndrome (DCS) with CTS combined with C8 - T1 CRS, so as to verify the double - nerve compression theory, provide evidence-based basis for clinical treatment. Methods: Retrospective analysis of 30 subjects per group (CTS, CRS, DCS, controls) from a neurophysiological database. Parameters included distal motor latency (DML1-wrist, DML2-elbow), compound muscle action potential (CMAP1, CMAP2), wrist-elbow motor conduction velocity (MCV), and F-wave latency. Results: For each indicator, both the CTS group and the DCS group showed statistically significant differences from the normal group. When comparing between the CTS group and the DCS group, there were no statistically significant differences in all data indicators. When comparing the CRS group with the normal group, there were no statistically significant differences in DML1 and DML2, but there were statistically significant differences in the shortest latency of the F wave and the motor conduction velocity (MCV). Conclusion: Double compression does not cause more severe damage to the nerve compared with simple distal compression. Distal compression of the median nerve causes more severe damage to the peripheral nerve than proximal compression. For patients with double compression syndrome, clinical treatment should prioritize the treatment of the distal compression site.